The nature, roles, uses, and impacts of accounting systems in the Real Liceo of Lucca in the nineteenth century. (2nd January 2022) - Capocchi, Alessandro; Orlandini, Paola; Pierotti, Mariarita; Amelio, Stefano
ABSTRACT: This study aims to advance the literature by examining how accounting systems were used in the management of the Real Liceo in Lucca during the nineteenth century. It considers rare documents, statutes, and accounting books concerning the administration of the Real Liceo from 1819 to 1848. Focused on the importance of academic and educational organisation at the individual and societal levels, in line with Foucault's works and theories, this research critically analyses the social and technical practice of accounting within the context of the Real Liceo, especially the nature, roles, uses, and impacts of accounting information in allocating resources and evaluating accountability.